C1‐Symmetric Atropisomeric NHC Palladium(II) Complexes: Synthesis, Resolution and Characterization. Issue 17 (14th July 2021) - Kong, Lingyu; Chou, Yajie; Jean, Marion; Albalat, Muriel; Vanthuyne, Nicolas; Nava, Paola; Humbel, Stéphane; Clavier, Hervé
Abstract: Series of chiral palladium(II) allyl and cinnamyl complexes bearing a C 1 ‐symmetric N‐heterocyclic carbenes were synthesized from achiral precursors. The chirality of theses complexes results from the formation of the carbene‐palladium bond which restricts the rotation of dissymmetric N ‐aryl substituents of the NHC and thus creates an axis of chirality. Chiral HPLC at preparative scale enabled the resolution of racemic complexes and provided a straightforward access to complexes with excellent enantiopurities (>99.5% ee). Enantiopure complexes were studied by crystal X‐ray diffraction and electronic circular dichroism (ECD). Their configuration stabilities were investigated both experimentally and theoretically through the determination of the rotational barrier values. These complexes were tested for the intramolecular α‐arylation of amides, with a moderate chiral induction (up to 54% ee). Abstract :